Trends of critical care management of obstetric patients in a tertiary hospital in sub-Saharan Africa - Onyekwulu, Fidelis A.; Okeke, Tochukwu C. (International Journal of Research in Medical Sciences, 2019)
Background: The maternal mortality rate in sub-Saharan Africa is high compared to other regions of the world. Management of critically ill obstetric patients is very challenging. We therefore evaluate the trends, clinical characteristics and outcome of the obstetric patients admitted into the intensive care unit of a tertiary hospital in sub Saharan Africa. Methods: This was a 9- year retrospective study carried out at the multidisciplinary Intensive Care Unit (ICU) of a University Teaching Hospital which serves as a referral centre for the south east region of the country. Data were collected from the patients’ record, ICU admission and discharge register. Also collected was data concerning labor ward admission and deliveries. Data was analyzed using SPSS Version 17 (SPSS Inc., Chicago, IL, USA). Results: The total admission into the ICU during the study period was 1243 patients of which 73 (5.87%) were obstetric patients. They were between the ages of 17 and 54 years with mean of 32.05±5.96 years. The total number of deliveries within the period was 11224 (1247 per year). The commonest obstetric cases admitted into the ICU were (pre) eclampsia 28.8% followed by obstetric hemorrhage 24.7%. The overall mortality rate in this study was 39.7%. The commonest intervention carried out in the ICU was mechanical ventilation. Conclusions: The two leading indications for ICU admission and maternal mortality are (pre)eclampsia and obstetric hemorrhage.